International Conference “Actual Problems of Analysis, Differential Equations and Algebra” (October 16-19, 2019, Astana, Kazakhstan) - Burenkov, Victor; Ospanov, Kordan (Eurasian Mathematical Journal, 2018)
International Conference “Actual Problems of Analysis, Differential Equations and Algebra” (October 16-19, 2019, Astana, Kazakhstan)